DRIVING TOURIST INTENTIONS THROUGH USER-GENERATED CONTENT: EVIDENCE FROM STRUCTURAL EQUATION MODELING - Sarah Madaniah; Eunike Al Grea; Atika Arfa Matondang; Syafrizal Helmi Situmorang (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
This study investigates the impact of User-Generated Content (UGC) on tourists' visit intentions and decision-making. Data were collected through online surveys with purposive sampling, involving 133 participants in Medan, North Sumatra, focusing on visit intentions to the Tjong A Fie Mansion. The proposed model was tested using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that trust in UGC (TUGC) substantially affects visit intention (VI). Emotional UGC (EUGC) has a small effect on visit intention and strongly affects trust in UGC. In contrast, factual UGC (FUGC) has no significant impact on either trust in UGC or visit intention. EUGC demonstrates a strong mediation effect on visit intention through trust in UGC, while FUGC shows a low mediation effect.